PENDAMPINGAN GURU DALAM PENGEMBANGAN LKPD KOLABORATIF MELALUI OUTINGCLASS DI PERUSAHAAN GREENHOUSE BERBASIS TEKNOLOGI KOREA - Siti Nurul Afifah; Nining Pambudi Astuti; Kurniawan Kurniawan (FIP UNIRA MALANG, 2026)
The rapid development of technology and the implementation of the Deep Learning Curriculum require teachers to design contextual, collaborative, and project-based learning materials. However, many teachers still face challenges in creating innovative and integrated Lembar Kerja Peserta Didik (LKPD) across subjects. This community service activity aimed to improve the competence of cross-subject teachers at SMP Gracia Nusantara School Malang in developing collaborative LKPD based on Smart Eco-Farming through a Project-Based Learning (PjBL) approach. The program was carried out in three stages: observation, training on Canva application, and mentoring for LKPD development contextualized through a field study at PT DMC Food Indonesia. The findings revealed a significant improvement in teachers’ understanding of PjBL and Deep Learning principles, as well as their ability to design interactive and digital-based LKPD, with an average quality score of 88% (very good category). The field study strengthened the collaboration between schools and industry in promoting technological literacy and sustainability awareness among students and teachers. This program is recommended to be sustained and replicated in other educational institutions to enhance teachers’ pedagogical innovation. The authors express appreciation to SMP Gracia Nusantara School Malang and PT DMC Food Indonesia for their valuable support and cooperation.